Hydrogen Tunneling Exhibiting Unexpectedly Small Primary Kinetic Isotope Effects - Roque, Jose P. L.; Nunes, Claudio M.; Schreiner, Peter R.; FAUSTO, RUI (Wiley - VCH Verlag GmbH, 2024)
Probing quantum mechanical tunneling (QMT) in chemical reactions is crucial to understanding and developing new transformations. Primary H/D kinetic isotopic effects (KIEs) beyond the semiclassical maximum values of 7–10 (room temperature) are commonly used to assess substantial QMT contributions in one-step hydrogen transfer reactions, because of the much greater QMT probability of protium vs. deuterium. Nevertheless, we report here the discovery of a reaction model occurring exclusively by H-atom QMT with residual primary H/D KIEs. 2-Hydroxyphenylnitrene, generated in N2 matrix, was found to isomerize to an imino-ketone via sequential (domino) QMT involving anti to syn OH-rotamerization (rate determining step) and [1,4]-H shift reactions. These sequential QMT transformations were also observed in the OD-deuterated sample, and unexpected primary H/D KIEs between 3 and 4 were measured at 3 to 20 K. Analogous residual primary H/D KIEs were found in the anti to syn OH-rotamerization QMT of 2-cyanophenol in a N2 matrix. Evidence strongly indicates that these intriguing isotope-insensitive QMT reactivities arise due to the solvation effects of the N2 matrix medium, putatively through coupling with the moving H/D tunneling particle. Should a similar scenario be extrapolated to conventional solution conditions, then QMT may have been overlooked in many chemical reactions.
Keywords: Hydrogen Tunneling; Reactive Intermediates; Kinetic Isotopic Effects; Matrix-isolation; and Solvation Effects